The influence of hydrophilic mPEG segment on formation, morphology, and properties of PCL‐mPEG microspheres. Issue 6 (14th September 2017) - He, Yu; Liu, Ping; Shi, Chen; Liu, Yongwei; Liu, Songxiang; Feng, Xiaobo; Fu, Dehao
Abstract: This research displayed the differences of formation process, morphology, degradation, and release behaviors between PCL and PCL‐mPEG microspheres. Lysozyme loaded microspheres were prepared by double emulsion evaporation method, and the double droplets transformation process was observed and compared under microscope. Microspheres morphology, in vitro degradation and release behaviors were evaluated by scanning electron microscope, gel permeation chromatography, and bicinchoninic acid protein assay kit. PCL‐mPEG microspheres got a rough surface and the outer water phase penetrated into PCL‐mPEG double droplet easier than PCL during the transformation, accompanied with a high broken percentage and size swelling. PCL‐mPEG microspheres get a faster degradation/erosion rate than PCL microspheres, and the rate was in direct proportion to mPEG chain length. In vitro release analysis showed that PCL‐mPEG microspheres get a faster release rate than PCL microspheres, and the rate was also in direct proportion to mPEG chain length.